80/20 your organization using AHP for quantitative decision making. (2022) - Kharub, Manjeet; Kattekola, Samved; Pendyala, Sai Krishna
Abstract: When it comes to economics, the Pareto Principle (80/20 rule) states that 80 percent of an economy's output is attributable to 20 percent of its input. This implies that concentrating on a small number of critical variables rather than a large number of inconsequential factors will provide the greatest results. This has been used in industrial sectors to help the organisation and its workers make better choices in order to increase the efficiency of the company's operations. This rule is being considered in order to make the best use of personnel, techniques, equipment, materials, and money in order for an organisation to improve production while simultaneously reducing needless labour, which is the primary goal of this article. The Analytical Hierarchy Process (AHP) Method may help to improve the effectiveness of this concept. This method chooses variables based on a hierarchy or need, allowing qualitative data to be represented quantitatively via the use of a numerical representation. Through this, the concept may be applied to the industry, and the greatest results can be achieved in this way for the company.